KREATIVITAS GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN DI SD NEGERI 2 BAMBAPUN - Sitti Nuralan (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to find out how the creativity of teachers in the development of learning media at SD Negeri 2 Bambapun. This type of research was qualitative research conducted at SD Negeri 2 Bambapun.The subject of this study was the principal, teachers and students of class V. Data collection techniques in this study, namely using observation sheet interview guidelines and documentation. Data analysis in this study was conducted by reducing, presentation, conclusion and validity of data. The results of this study are about the Teacher's creativity in the development of student learning media in SD Negeri 2 bambapun are seen from the creativity of the teacher in the SD Negeri 2 Bambapun in developing teacher learning media has been creative, it can be seen in person, process, products and also the development of learning media and factors - factors found by the teacher in developing media with the results of supporting factor research, namely the positive support of the principal and the inhibitory factor is the lack of human resources facilitators or speakers guide teachers in the development of learning media.